Customer Experience and Guest Repurchase Intention at Rocky Plaza Hotel: Pengalaman Pelanggan dan Niat Pembelian Ulang Tamu di Hotel Rocky Plaza - Wulandari Wulandari; Asmar Yulastri; Ernawati Ernawati; Rahmiati Rahmiati (Academia Open, 2025)
General Background: Customer experience is a crucial factor in the hospitality industry as it influences customer loyalty and repurchase decisions. Specific Background: In Padang, four-star hotels, including Rocky Plaza Hotel, face fluctuating occupancy rates that have not consistently met targets, despite strategic locations. Knowledge Gap: While prior studies confirm the link between customer experience and repurchase intention in various regions, limited research focuses on four-star hotels in West Sumatra, particularly regarding the integration of sensory, emotional, and social dimensions of customer experience. Aims: This study aims to examine the influence of customer experience on repurchase intention among guests at Rocky Plaza Hotel Padang. Results: Using purposive sampling with 98 respondents, data analyzed through simple linear regression revealed that customer experience was categorized as very good (80.61%) and repurchase intention as very good (83.67%). The regression results showed a significant influence, with customer experience explaining 53.6% of the variance in repurchase intention. Novelty: This study uniquely combines three indicators of customer experience (sensoric, emotional, and social) with four indicators of repurchase intention (transactional, referential, explorative, and preferential), while integrating occupancy data for contextual depth. Implications: Findings highlight that enhancing personalized services, emotional connections, and social interactions can strengthen loyalty, offering practical insights for hotel management and contributing to service marketing and CRM literature in the local context. Highlights: Customer experience significantly drives repurchase intention (53.6%). Emotional, sensory, and social aspects shape guest loyalty. Novel framework integrates hotel occupancy data with survey analysis. Keywords: Customer Experience, Repurchase Intention, Hospitality, Hotel Loyalty, Service Marketing